TINJAUAN HUKUM EKONOMI SYARIAH TERHADAP BAI’ AL-TAWARRUQ PADA JUAL BELI PADI (GABAH) DI DESA SELAT KECAMATAN NARMADA - Fujiana Maulani Azizah; Syukri Syukri; Lalu Fahrizal Cahyadi (STIT Sunan Giri Bima, 2023)
This research is motivated by the Bai' Al-Tawarruq system whose permissibility is still being debated by scholars, but this system is still widely used in payment for buying and selling rice (grain) so it is important to study and provide perspective. There are 2 characteristics of Bai' Al-Tawarruq, namely Tawarruq Fiqhi/Haqiqi and Tawarruq Munazzam and in the context of Tawarruq what is allowed is Tawarruq Fiqhi where the transaction process is not planned in advance while in Tawarruq Munazzam the transaction process is planned forward and this is not allowed. This study aims to analyze and find out the review of sharia economic law on the practice of Bai' Al-Tawarruq in buying and selling rice (grain). The type of research used is qualitative research that is normative empirical with the type of data source using primary data, namely respondents and social phenomena and secondary data sources using literature, documents and manuscripts and data collection methods in the form of observation, interviews and documentation. The data analysis technique uses data triangulation with the theory of Milles and Hubermant. The results showed that (1) there are 2 sales systems used in buying and selling rice (grain), namely (a) buying and selling with rice still in the fields and (b) buying and selling with rice seeds that have been weighed. Then there are 2 payment systems, namely (a) paid directly/cash (b) paid indirectly/debt. Then the factors causing the debt payment system to be used are (a) farmers and buyers (penendak) know each other well (b) at the time of the transaction the farmers did not need money/were not going to work on their fields yet, (2) the law from bai' al-tawarruq was still debated by the scholars', the Shafi'i school allows it and some Maliki schools do not allow it. After the researcher analyzed the practices that occurred in Selat Village with the law from Bai' Al-Tawarruq, the researcher found results that the practices that occurred in Selat Village were included in the practice of Bai' Al-Tawarruq fiqhi and the law was permissible.